(untitled) (Islamic Sciences Journal, 2023)
This study aims to: Explain the importance of following the Prophetic method in raising girls and its impact on building human values. The reason for choosing the research is that the issue of bringing up girls constitutes a great intellectual and social space, and the loss of their religious and social rights, in addition to the bad treatment of girls, and their lack of equality with males in education and appreciation. The problem of the research: This study came to clarify the problem of “women’s education” by answering the question: Is there a text from the Holy Qur’an or the Prophet’s Sunnah that prohibits girls’ education? The limits of the research: The Prophet, peace be upon him, paid great attention to the education of girls and boys, and he singled out girls by directing practical messages, and setting the right approach in building the personality of a righteous woman, and taking several methods in preparing her, in terms of her education, ideologically, morally, culturally and scientifically, and developing human values ​​in her; Because it is the nucleus of society Research plan: The research is divided into an introduction, a preface and four sections, then a conclusion that contains the most important results and then recommendations are presented.